The use of oncolytic virotherapy in the neoadjuvant setting. Issue 4 (12th April 2022) - Thomas, Raquela J; Bartee, Eric
Abstract : Surgical removal of tumors remains a front-line therapy for many types of cancer. However, this treatment often fails to eradicate disease due to either recurrence of the original tumor or development of distant micrometastases. To address these challenges, patients are often given non-curative treatments presurgery with the intent of improving surgical outcomes. These treatments, collectively known as neoadjuvant therapies, have traditionally focused on the presurgical use of chemotherapeutics. Recently, however, a variety of immunotherapies have also been identified as potentially effective in the neoadjuvant setting. One of these immunotherapies is oncolytic virotherapy, whose clinical use has exploded with the Food and Drug Administration approval of Talimogene Laherparepvec. This review summarizes both the preclinical and clinical literature examining the use of oncolytic virotherapy in the neoadjuvant setting for different types of cancers and discusses some of the major questions that still need to be addressed in order for this unique use of immunotherapy to become clinically viable.